Understanding youth disaster recovery: The vital role of people, places, and activities. (June 2017) - Cox, Robin S.; Scannell, Leila; Heykoop, Cheryl; Tobin-Gurley, Jennifer; Peek, Lori
Abstract: As disasters escalate in frequency and severity, children and youth are among those most at risk for resulting adverse psychological, social, health, and educational effects. Although there is growing interest in the vulnerabilities and capacities of youth who have experienced disaster, research focusing on their lived experiences during the recovery period remains sparse. In response to this knowledge gap, youth between the ages of 13–22 were invited to participate in workshops spanning one to four days, where they used art, music, photography, videography, and other means to articulate their experiences of post-disaster recovery. The research took place in four disaster-affected communities in the United States and Canada, including Joplin, Slave Lake, Calgary, and High River. Youth stories revealed key people, places, and activities that supported their recovery, and the mechanisms through which those supports had a positive impact. Examining youth perspectives is important to concretize and contextualize theories of disaster recovery. Highlights: Youth's lived experiences of disasters are relatively under-examined. Youth from four communities shared perspectives on disaster recovery using arts-based methods. Key people aided their recovery though instrumental, emotional, and companionship support. Youth identified places that supported their recovery by satisfying psychological needs. Youth identified a range of activities and the means through which they aided in their recovery.